THE ANALYSIS OF BANKING GOVERNANCE IN INDONESIA: THE FINANCIAL SERVICES AUTHORITY PERSPECTIVE - Rudy Hartanto; Pupung Purnamasari (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2019)
The purpose of this study is to examine the factors that influence the ranking of banking governance in Indonesia. This study uses the perspective of regulatory authority of financial services concerning self-assessment of bank governance as regulated in Regulation of Financial Services Authority Number (POJK). The data in this study using the report of banking governance in 2014-2017 with a sample obtained as many as 294 banks. Hypothesis testing technique is done by using ordinal regression analysis. The results showed that the variable owner, ROA, asset, and status have a positive effect on GCG. In contrast, the leverage in this study showed a negative influence on GCG. Testing the growth and age does not affect the level of banking governance